Quantifying Asthenospheric and Lithospheric Controls on Mafic Magmatism Across North Africa. (22nd July 2019) - Ball, P. W.; White, N. J.; Masoud, A.; Nixon, S.; Hoggard, M. J.; Maclennan, J.; Stuart, F. M.; Oppenheimer, C.; Kröpelin, S.
Abstract: African basin‐and‐swell morphology is often attributed to the planform of subplate mantle convection. Across North Africa, the coincidence of Neogene and Quaternary (i.e., <23 Ma) magmatism, topographic swells, long wavelength gravity anomalies, and slow shear wave velocity anomalies within the asthenosphere provides observational constraints for this hypothesis. Admittance analysis of topographic and gravity fields corroborates the existence of subplate support. To investigate quantitative relationships between intraplate magmatism, shear wave velocity, and asthenospheric temperature, we collected and analyzed a suite of 224 lava samples from Tibesti, Jabal Eghei, Haruj, Sawda/Hasawinah, and Gharyan volcanic centers of Libya and Chad. Forward and inverse modeling of major, trace, and rare Earth elements was used for thermobarometric studies and to determine melt fraction as a function of depth. At each center, mafic magmatism is modeled by assuming adiabatic decompression of dry peridotite with asthenospheric potential temperatures of 1300‐1360 °C. Surprisingly, the highest temperatures are associated with the low‐lying Haruj volcanic center rather than with the more prominent Tibesti swell. Our results are consistent with earthquake tomographic models which show that the slowest shear wave anomalies within the upper mantle occur directly beneath the Haruj center. This inference is corroborated by converting observed velocities into potential temperatures, which are in good agreement with those determined by geochemical inverse modeling. Our results suggest that North African volcanic swells are primarily generated by thermal anomalies located beneath thinned lithosphere. Key Points: Analyses of 224 samples of Neogene and Quaternary igneous rocks from Libya and Chad are presented Geochemical and seismic estimates of asthenospheric temperature show that Haruj swell is hotter than Tibesti swell Combination of warm asthenosphere and thinned lithosphere generates regional uplift of North African swells